Integrating AI Competencies into Teacher Education Programs - Eguchi, Amy; George, Stacy; Fraga, Lucretia; Black, Nancye Blair; Blackwood, Alecia; Dempsey, J. Camille; Kasun, G. Sue (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
The rapid advancement and integration of artificial intelligence (AI) into our everyday lives, work, and classrooms have added demands for PK-12 education to ensure that students are given opportunities to obtain AI competencies essential for responsible participation in the AI-driven future. AI literacy encompasses technical knowledge, ethical awareness, and critical evaluation of AI tools, as well as the ability to collaborate with AI systems in creative and productive ways. Research highlights the importance of age-appropriate approaches that address foundational AI knowledge, data literacy, ethics, problem-solving, and creativity, ensuring students can both use, analyze, critically evaluate, and design AI solutions for real-world challenges. This not only requires schools to prepare learners with AI competencies, but also colleges and universities to ensure that we prepare our preservice teachers to be AI-ready, who can integrate technological, pedagogical, and content knowledge in classroom practice. This paper highlights the importance of purposefully integrating AI competencies into teacher education programs and offers practical examples of how such integration can be achieved.